Ambulance use in Pakistan: an analysis of surveillance data from emergency departments in Pakistan. Issue 2 (December 2015) - Zia, Nukhba; Shahzad, Hira; Baqir, Syed; Shaukat, Shahab; Ahmad, Haris; Robinson, Courtland; Hyder, Adnan; Razzak, Junaid
Abstract Background The utilization of ambulances in low- and middle-income countries is limited. The aim of this study was to ascertain frequency of ambulance use and characteristics of patients brought into emergency departments (EDs) through ambulance and non-ambulance modes of transportation. Methods The Pakistan National Emergency Departments Surveillance (Pak-NEDS) was a pilot active surveillance conducted in seven major tertiary-care EDs in six main cities of Pakistan between November 2010 and March 2011. Univariate and multivariate logistic regression was performed to investigate the factors associated with ambulance use. Results Out of 274, 436 patients enrolled in Pak-NEDS, the mode of arrival to the ED was documented for 94. 9% (n = 260, 378) patients, of which 4.1% (n = 10, 546) came to EDs via ambulances. The mean age of patients in the ambulance group was significantly higher compared to the mean age of the non-ambulance group (38 ± 18.4 years versus 32.8 ± 14.9 years, p-value < 0.001). The most common presenting complaint in the ambulance group was head injury (12%) while among non-ambulance users it was fever (12%). Patients of all age groups were less likely to use an ambulance compared to those >45 years of age (p-value < 0.001) adjusted for gender, cities, hospital type, presenting complaint group and disposition. The adjusted odds ratio of utilizing ambulances for those with injuries was 3.5 times higher than those with non-injury complaints (p-value < 0.001). Patients brought to the ED by ambulance were 7.2 times more likely to die in the ED than non-ambulance patients after adjustment for other variables in the model. Conclusion Utilization of ambulances is very low in Pakistan. Ambulance use was found to be more among the elderly and those presenting with injuries. Patients presenting via ambulances were more likely to die in the ED.